The Interactive Effect of Organizational Identification and Organizational Climate on Employees' Taking Charge Behavior: A Complexity Perspective. (28th July 2021) - Liu, Yun; Chen, Lingjuan; Zhao, Liangjie; Li, Chengai
Abstract : In the view of complexity theory, the emergency behavior of individual is nonlinear and influenced not only by individual variables but also by many other environmental variables. Based on complexity perspective, this article explored why employees' taking charge behavior occurs in organizations from a multilevel approach. Specifically, this study has explored the cross-level interactive effect of organization-level factor (organizational justice climate and psychological safety climate) and individual-level factor (organizational identification) on employees' taking charge behavior. Using a total of 806 valid matching questionnaires from 91 firms in China, this study found that first, organizational identification is positively related with employees' taking charge behavior. Second, distributive justice climate positively moderates the influence of organizational identification on employees' taking charge behavior. Third, psychological safety climate negatively moderates the influence of organizational identification on employees' taking charge behavior. According to our results, organizational policies and practices should be made to foster employees' identification with the organization, to construct a fair environment within the organization, and to convince employees that taking charge behavior will not entail political risks, especially for those employees with low organizational identification.